2019
DOI: 10.3390/plants8120608
|View full text |Cite
|
Sign up to set email alerts
|

United Forces of Botanical Oils: Efficacy of Neem and Karanja Oil against Colorado Potato Beetle under Laboratory Conditions

Abstract: Neem and karanja oil are the most promising botanical insecticides in crop protection nowadays. Given that information about the insecticidal abilities of these oils is lacking, the aim was to explore the effects of neem and karanja oil binary mixtures. The insecticidal activity of NeemAzal T/S (Trifolio-M GmbH, Lahnau, Germany) (neem oil), Rock Effect (Agro CS a.s., Česká Skalice, Czech Republic) (karanja oil), and their binary mixes (at 1:1, 1:2, and 2:1 volume ratios) against the larvae of the Colorado pota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…The leaf area consumed by CPB larvae differed significantly between all treatments (except the lowest doses of spinosad and spinetoram) and the untreated control in the first two days after application (Table 4). The results obtained confirm the findings of others [30,32], who observed that CPB larvae treated with neem oil showed reduced feeding, resulting in lower leaf damage compared to the control. Because of the antifeedant properties of azadirachtin, it was beneficial to analyze defoliation damage along with efficacy.…”
Section: Laboratory Trialsupporting
confidence: 91%
See 2 more Smart Citations
“…The leaf area consumed by CPB larvae differed significantly between all treatments (except the lowest doses of spinosad and spinetoram) and the untreated control in the first two days after application (Table 4). The results obtained confirm the findings of others [30,32], who observed that CPB larvae treated with neem oil showed reduced feeding, resulting in lower leaf damage compared to the control. Because of the antifeedant properties of azadirachtin, it was beneficial to analyze defoliation damage along with efficacy.…”
Section: Laboratory Trialsupporting
confidence: 91%
“…This result does not coincide with the result of others [12] that investigated the combination of azadirachtin and spinosad (12.5% + 33.33% of the full dose) and stated that an independent synergism was found in the laboratory experiment, although they did not use any calculation methods. The fact that azadirachtin is acting as an antifeedant [30,32] and that spinosad is acting better as stomach than contact poison [34] could explain the established joint action of two insecticides applied in combination. In spite of that the joint action is classified as antagonism and, given into account that very low doses (25% + 5% of the full dose) were applied, the efficacy of combination was significant.…”
Section: Laboratory Trialmentioning
confidence: 99%
See 1 more Smart Citation
“…Other ways of application which might increase the efficacy, for instance systemically through soil application (Pavela et al, 2004;Karanja et al, 2015) or encapsulation to protect azadirachtin against degradation (Forim et al, 2013;Chaudhary et al, 2017), are not yet registered with the exception of soil application against fungus gnats (BVL, 2021). The efficacy might be increased by combining neem with synergistic products such as karanja oil (Kovarikova & Pavela, 2019) or with a contact knock-down insecticide such as pyrethrum. This can ensure a higher efficacy as well as a good resistance management.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the efficacy of neem and karanja oil in binary mixtures against CPB larvae was investigated [99]. The experiment demonstrated a synergistic effect in laboratory trials.…”
Section: Environmentally Friendly Insecticides Synergists and Their C...mentioning
confidence: 99%